Pengajaran Disiplin Gereja berdasarkan pengakuan-pengakuan Reformed - Cathryne Berliana Nainggolan (Universitas Pelita Harapan, 2026)
Church discipline is a sensitive topic because it is directly related to the holiness of believers’ lives within the church. Various theological angles have emphasized the importance of a proper understanding and faithful practice of church discipline. However, a comprehensive exploration of church discipline based on the Reformed confessions has not yet been sufficiently developed. Therefore, this paper aims to explore the doctrine of church discipline as articulated in the Reformed confessions, with particular attention to the Belgic Confession, the Heidelberg Confession, and the Westminster Standards. This study employs a dialectical and analytical approach to examine the teaching of church discipline within the Reformed traditions. The exploration of these confessional documents demonstrates that church discipline is not merely a corrective measure but an essential ecclesial practice. It serves to preserve the holiness and purity of the church, uphold doctrinal faithfulness, and reflect the church’s identity as the body of Christ. Thus, church discipline is understood as a vital means through which the church faithfully lives out its calling before God and the world.